2013
DOI: 10.2174/1875414701003010151
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Effects in Soil of Cry Proteins from Bacillus thuringiensis: Influence of Physicochemical and Biological Characteristics of Soil

Abstract: Bacillus thuringiensis (Bt) is a useful alternative or supplement to synthetic chemical pesticides in agriculture, forest management, and control of mosquitoes and some other biting insects. When modified Bt cry genes are inserted into a plant species (e.g., corn, cotton, potato, canola, rice), the plant expresses active larvicidal proteins in its tissues. The toxins continue to be synthesized during growth of the plants, making the plant toxic to various insect pests throughout their life or as biomass incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 198 publications
(312 reference statements)
0
13
0
Order By: Relevance
“…However, the effects could vary under different soil types and agro-climatic conditions (Chen et al 2011). Soil types, clay and organic matter contents could influence the degradation and binding of cry proteins in soils Saxena et al 2010).…”
Section: Effect Of Bt-cotton On Soil Enzymatic Activitiesmentioning
confidence: 99%
“…However, the effects could vary under different soil types and agro-climatic conditions (Chen et al 2011). Soil types, clay and organic matter contents could influence the degradation and binding of cry proteins in soils Saxena et al 2010).…”
Section: Effect Of Bt-cotton On Soil Enzymatic Activitiesmentioning
confidence: 99%
“…In addition, secondary pests, such as mirids and spider mites, may pose a new challenge in transgenic crop fields 15 - 23 . Furthermore, the negative impacts of Bt toxins derived from Bt transgenic crops on soil organisms should not be neglected 24 - 27 . Therefore, it is essential to identify new types of exogenous genes and even alternative pest control strategies for transgenic plants.…”
Section: Introductionmentioning
confidence: 99%
“…The potential impacts of Bt plants on soil organisms depend, at least in part, on the persistence of the transgenic‐derived protein and its biological activity in soil. Research has shown that Bt toxins can bind to clay particles and humic substances from soils, which renders the proteins resistant to biodegradation, but with retention of larvicidal activity (Zwahlen et al 2003; Clark et al 2005; Viktorov 2008; Saxena et al 2010). Most studies have suggested that Bt proteins from transgenic plants break down relatively rapidly in the early stage after entering soil, and that only a small amount of them can remain for long, so that Bt proteins do not bio‐accumulate in soil (Ahmad et al 2005; Li et al 2007; Icoz and Stotzky 2008a, 2008b; Margarit et al2008; Rauschen et al 2008; Shan et al 2008; Daudu et al 2009; Zurbrügg et al 2010).…”
Section: Introductionmentioning
confidence: 99%